Antioxidant-Rich Natural Raw Materials in the Prevention and Treatment of Selected Oral Cavity and Periodontal Diseases - Pytko-Polończyk, Jolanta; Stawarz-Janeczek, Magdalena; Kryczyk-Poprawa, Agata; Muszyńska, Bożena (Antioxidants, 2021)
Antioxidant-rich natural raw materials have been used for thousands of years in traditional medicine. In the past decade, there has been increasing interest in naturotherapy, which is a practice of using products with a natural origin. Natural products can be effective in the treatment and prevention of oral and dental diseases, among others. Such raw materials used in dentistry are characterized by antioxidant, anti-inflammatory, antibacterial, antiviral, antiedematous, astringent, anticoagulant, dehydrating, vitaminizing, and—above all—regenerative properties. Reports have shown that a relationship exists between oral diseases and the qualitative and quantitative composition of the microbiota colonizing the oral cavity. This review aimed to analyze the studies focusing on the microbiome colonizing the oral cavity in the context of using natural raw materials especially herbs, plant extracts, and isolated biologically active compounds as agents in the prevention and treatment of oral and periodontal diseases such as dental caries as well as mucosal changes associated with salivary secretion disorder. The present work discusses selected plant ingredients exhibiting an antioxidant activity with potential for the treatment of selected oral cavity and periodontal diseases.